Sociolinguistics a very short introduction - Edwards, John 1947 December 3- (Very short introductions, 2013)
In this Very Short Introduction, John Edwards offers the most up-to-date brief overview available of sociolinguistics, with side trips into the sociology of language and psycholinguistics. He considers such topics as the different social evaluations of languages and dialects, the loaded significance of names, and the importance of politically-driven language planning and policy. The relationship between language and gender, sexist language, the language of poverty, and the intertwining of language and religion are also dealt with here. Edwards stresses that, while linguists see all dialects as equally valid, in the wider world powerful attitudes have always placed language varieties in social hierarchies. The author also looks at language more broadly, examining the ways in which languages rise or fall, the attempts to revive flagging or endangered varieties, the reasons why some languages came to dominate others, and the special dynamics that affect contact between "big" and "small" languages.